The influence of supplementation with Rhodiola rosea L. extract on selected redox parameters in professional rowers - Skarpanska-Stejnborn, A.; Pilaczynska-Szczesniak, L.; Basta, P.; Deskur-Smielecka, E. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
The aim of this study was to investigate the effect of Rhodiola rosea supplementation on the balance of oxidants and antioxidants in the serum and erythrocytes of competitive rowers. This double-blinded study included 22 members of the Polish Rowing Team who were participating in a preparatory camp. Participants were randomly assigned to the supplemented group (n = 11), who received 100 mg of R. rosea extract twice daily for 4 wk, or the placebo group (n = 11). At the beginning and end of the study, participants performed a 2,000-m maximum test on a rowing ergometer. Blood samples were taken from the antecubital vein before each exercise test, 1 min after completing the test, and after a 24-hr restitution period. The following redox parameters were assessed in erythrocytes: superoxide dismutase activity, glutathione peroxidase activity, and thiobarbituric-acid-reactive substances concentrations. In addition, creatine kinase activity and total antioxidant capacity were measured in plasma samples, lactate levels were determined in capillary blood samples, and uric acid concentrations were measured in serum. After supplementation, the total plasma antioxidant capacity was significantly higher (p = .0002) in the supplemented group than in the placebo group, and superoxide dismutase activity in erythrocytes directly after and 24 hr after the ergometry was significantly (p = .0461) lower in athletes receiving R. rosea extracts than in the placebo group. In conclusion, supplementation with R. rosea increased antioxidant levels in the plasma of professional rowers but had no effect on oxidative damage induced by exhaustive exercise.